GAnet: genetic algorithm platform for pipe network optimisation - Morley, M.S; Atkinson, R.M; Savić, D.A; Walters, G.A (Advances in engineering software (1992), 2001)
The marriage of object-oriented programming techniques and genetic algorithms (GAs) provides a uniquely flexible environment for the development of evolution programs with technical applications. Computerised representations of hydraulic network models are used in various guises throughout the water industry. As well as being commonly linked to relational databases to form asset management systems and to geographic information systems (GIS) to provide visualisation and mapping facilities, common applications include modelling the hydraulic performance of the network and use in network optimisation applications. This paper describes an architecture for an integrated optimisation application, GAnet, which comparises a GA application, a GIS and a hydraulic network solver.